2022
DOI: 10.1002/ppul.26020
|View full text |Cite
|
Sign up to set email alerts
|

Early predictors of lung necrosis severity in children with community‐acquired necrotizing pneumonia

Abstract: Objective To analyze baseline clinical and laboratory characteristics and explore the possible predictors of lung necrosis severity in children with community‐acquired necrotizing pneumonia (NP). Methodology This retrospective observational study was performed in a tertiary referral center. A total of 104 patients aged <15 years with community‐acquired pneumonia and radiologically confirmed NP by computed tomography (CT) were included. Patients were classified into the mild, moderate, or massive necrosis group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
0
7
1
3
Order By: Relevance
“…Therefore, LDH is also often used as a predictor of severe pneumonia. 18 , 19 A retrospective analysis of NP by Li et al 11 found that CRP is an independent predictor of the degree of lung necrosis. CRP > 48.35 mg/L had a high predictive value for the diagnosis of NP, according to Qian et al 7 Zhou et al 20 found that WBC and CRP in the NP group caused by Mycoplasma pneumoniae were significantly higher than those in non-NP group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, LDH is also often used as a predictor of severe pneumonia. 18 , 19 A retrospective analysis of NP by Li et al 11 found that CRP is an independent predictor of the degree of lung necrosis. CRP > 48.35 mg/L had a high predictive value for the diagnosis of NP, according to Qian et al 7 Zhou et al 20 found that WBC and CRP in the NP group caused by Mycoplasma pneumoniae were significantly higher than those in non-NP group.…”
Section: Discussionmentioning
confidence: 99%
“…More than 30% necrosis was included in the MNP group, and no more than 30% necrosis was included in the non-MNP group. 11 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The common clinical manifestations of NP have no difference from those of uncomplicated pneumonia, including fever, cough, sometimes with chest pain, emesis, abdominal pain, dyspnea, anemia and fatigue [ 2 ]. But patients with NP have a more serious clinical course, longer duration of fever and length of stay, higher mortality, higher incidence of extra-pulmonary complications such as septic shock, respiratory failure and HUS and pulmonary complications such as parapneumonic effusion, pleural empyema, pyothorax, pneumothorax, pyopneumothorax and BPF [ 8 , 85 ]. PVL-positive Staphylococcus aureus is associated with high fever and an enhanced risk of purulent expectoration and hemoptysis [ 10 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Age and gender have no significant influence on the incidence of NP. The majority of reported cases are previously healthy and immunocompetent children [ 85 ]. When patients have flu-like symptoms, we should consider the possibility of viruses, especially during influenza season.…”
Section: Clinical Manifestationsmentioning
confidence: 99%